2017
DOI: 10.24875/ric.17002141
|View full text |Cite
|
Sign up to set email alerts
|

Non-Nutritive Sweeteners: Evidence on their Association with Metabolic Diseases and Potential Effects on Glucose Metabolism and Appetite

Abstract: There is ongoing debate concerning non-nutritive sweeteners, their usage, and their effects on metabolism. The association between non-nutritive sweeteners consumption, development of metabolic diseases, and changes in appetite-regulating hormones is not clear. The aim of this article is to present an overview of non-nutritive sweeteners and to examine the scientific evidence of their effects on glucose metabolism and appetite-regulating hormones. Some observational studies suggest an association between non-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“…This implies that subjects who are already obese or overweight (or its risk factors, or genetic predisposition to obesity or diabetes) consume more foods and drinks sweetened with LNCS in order to reduce or mitigate their condition, and not the reverse. In a recent review published by Romo-Romo et al (2017) [ 96 ], prospective cohort studies were condensed. The authors observed an attenuation of the association of LNCS with obesity and metabolic diseases, once the analysis includes adjustments of variables related to adiposity [ 96 ].…”
Section: Lncs Role In Body Weight Management and In Chronic Diseasmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that subjects who are already obese or overweight (or its risk factors, or genetic predisposition to obesity or diabetes) consume more foods and drinks sweetened with LNCS in order to reduce or mitigate their condition, and not the reverse. In a recent review published by Romo-Romo et al (2017) [ 96 ], prospective cohort studies were condensed. The authors observed an attenuation of the association of LNCS with obesity and metabolic diseases, once the analysis includes adjustments of variables related to adiposity [ 96 ].…”
Section: Lncs Role In Body Weight Management and In Chronic Diseasmentioning
confidence: 99%
“…In a recent review published by Romo-Romo et al (2017) [ 96 ], prospective cohort studies were condensed. The authors observed an attenuation of the association of LNCS with obesity and metabolic diseases, once the analysis includes adjustments of variables related to adiposity [ 96 ]. For this reason, Romo-Romo et al concluded that “evidence from prospective observational studies indicates that there might be a relationship between the consumption of LNCS sweetened beverages and metabolic disease development”.…”
Section: Lncs Role In Body Weight Management and In Chronic Diseasmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide NNS consumption has increased and Mexico exhibits a high proportion of nutritional products containing NNS [ 3 ]. The three most popular NNS are sucralose, aspartame and stevia; the first two being from synthetic origin (artificial) and the latter from natural sources [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dissociation between sweet taste and energy or plasma glucose may occur. 5,6 Hypoglycemia could occur in the condition of long-term fasting, possibly with the concomitant effect of incretins. We consider that the mechanisms of hypoglycemia, increased consumption of food and obesity may contribute, at least in part, to the conflicting and unexpected results of many clinical studies.…”
Section: The Timing Of Ingestion May Influence the Effect Of Nonnutrimentioning
confidence: 99%